Magnetism in an antiferromagnetic Ising nano-ladder under an applied transverse field. (3rd August 2019) - Kaneyoshi, T.
ABSTRACT: The phase diagram and magnetization curves of an antiferromagnetic Ising nano-ladder in an applied transverse field are investigated by using the effective-field theory with correlations. They are compared with those in the antiferromagnetic Ising ladder (or bulk). Some characteristic features, such as the reentrant phenomena, are found in these properties, when a finite transverse field h is applied or even when h  = 0.0.